2017
DOI: 10.1016/j.eml.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue fracture of tough hydrogels

Abstract: Abstract:Tough hydrogels of many chemical compositions have been developed in recent years, but their fatigue fracture has not been studied. The lack of study hinders further development of hydrogels for applications that require long lifetimes under cyclic loads. Examples include tissue engineering, soft robots, and stretchable electronics. Here we study the fatigue fracture of a polyacrylamide-alginate tough hydrogel. We find that the stress-stretch curve changes cycle by cycle, and reaches a steady state af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
186
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(204 citation statements)
references
References 56 publications
12
186
0
Order By: Relevance
“…This is consistent with the higher tan δ of semi‐IPN hydrogel, that is, higher energy dissipation efficiency. In comparison, the stress and the toughness of the IPN hydrogel of G25‐SA6 were much higher, and they decreased much more after the first compressing run, and then decreased gradually, similar as those reported in literature . The much higher strength and toughness of the IPN hydrogel should be contributed from the higher chain density and from the sacrificial ionic crosslinkings.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This is consistent with the higher tan δ of semi‐IPN hydrogel, that is, higher energy dissipation efficiency. In comparison, the stress and the toughness of the IPN hydrogel of G25‐SA6 were much higher, and they decreased much more after the first compressing run, and then decreased gradually, similar as those reported in literature . The much higher strength and toughness of the IPN hydrogel should be contributed from the higher chain density and from the sacrificial ionic crosslinkings.…”
Section: Resultssupporting
confidence: 86%
“…It has been suggested that there are some microstructure changes including disentanglements and sliding of polymer chains during the energy dissipation process, which results in decrease in strength of hydrogel . Therefore, the hydrogels were, respectively, compressed to 50% strain and to higher stain of 75%, and then recovered naturally to zero stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4,59,60 ] It is impossible to extract information on a hydrogel's fatigue resistance from single stress amplitude tests, stopped at arbitrary cycle numbers, though many studies have focused on this analysis. [40–42, 61–66 ] An overarching goal of this work is to understand the tensile fatigue properties of PVA with and without additives. To the author's knowledge, no such study focusing on full‐load spectrum cyclic, tensile testing has been published for a high‐strength synthetic hydrogel.…”
Section: Introduction Of Synthetic Hydrogelsmentioning
confidence: 99%
“…The energy dissipation is large when the hydrogel is loaded for the first time, but is often poorly reversible in the subsequent loading cycles, due to the irreversible nature of the bonds (e.g., covalent bonds), or the relatively short time allowed for recovery of the bonds (e.g., most mechanical motions work with periods shorter than a few minutes). Ultimately, all hydrogels suffer fatigue fracture, that is, the gradual extension of crack from an initial flaw under cyclic loads . The highest threshold for fatigue fracture of a double‐network, tough hydrogel reported up‐to‐date is about 400 J m −2 , still only 1/10 of its bulk fracture toughness …”
mentioning
confidence: 99%